2013
DOI: 10.1111/1440-1681.12157
|View full text |Cite
|
Sign up to set email alerts
|

Vascular effects of aldosterone: Sorting out the receptors and the ligands

Abstract: Aldosterone has actions far beyond its role as a renal regulator of sodium reabsorption, and broader mechanisms of action than simply a transcriptional regulator. Aldosterone has a number of vascular effects, including regulation of vascular reactivity and vascular growth and/or development. Aldosterone-mediated effects on vascular reactivity reflect a balance between its endothelial-dependent vasodilator effects and its direct smooth muscle vasoconstrictor effects. The endothelial vasodilator effects of aldos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…[27][28][29][30][31] However, the importance of GPER in regulation of lipoprotein metabolism in humans has been unexplored to date. Using a combination of human genetics and functional cellular biology, we found that the relatively common missense GPER P16L had a significant influence on LDL cholesterol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31] However, the importance of GPER in regulation of lipoprotein metabolism in humans has been unexplored to date. Using a combination of human genetics and functional cellular biology, we found that the relatively common missense GPER P16L had a significant influence on LDL cholesterol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low doses of aldosterone have been shown to exert direct effects on the vascular system by inducing oxidative stress, inflammation, hypertrophic remodeling, fibrosis and endothelial dysfunction, demonstrating that activation of the MR pathway by the ligand or the receptor activate different pathogenic mechanisms (Briet and Schiffrin, 2013;Feldman and Gros, 2013;McCurley and Jaffe, 2012). Following injury of vessels, MR activation has been shown to promote smooth muscle cells fibrosis via the activation of the Placental Growth Factor (PGF)/VEGF Receptor 1 (VEGFR1) Fig.…”
Section: Cscr: the Mineralocorticoid Pathway Hypothesismentioning
confidence: 99%
“…on vascular smooth muscle contractility, cardiac fibrosis, cardiac inotropy, and on growthand death-regulatory mechanisms. 2 Furthermore, beyond its direct transcriptional regulatory effects, aldosterone has been shown to trigger the activation of several second messenger signaling pathways traditionally associated with the activation of membrane receptors including regulation of cAMP metabolism, intracellular calcium concentrations, tyrosine kinases (both receptor and nonreceptor), and mitogen-activated protein kinases, especially the extracellular signal-regulated kinases. 3 Studies during the last several years have elucidated the molecular mechanisms mediating at least some of these cardiovascular effects.…”
Section: Mechanisms Of Effectmentioning
confidence: 99%